Evidence of novel plant‐species specific ammonia oxidizing bacterial clades in acidic South African fynbos soils. (27th February 2015) - Ramond, Jean‐Baptiste; Lako, Joseph D. W.; Stafford, William H. L.; Tuffin, Marla I.; Cowan, Don A.
<x xml:space="preserve">Abstract</x> Ammonia‐oxidizing bacteria (AOB) are essential in the biogeochemical cycling of nitrogen as they catalyze the rate‐limiting oxidation of ammonia into nitrite. Since their first isolation in the late 19th century, chemolithoautotrophic AOBs have been identified in a wide range of natural (e.g., soils, sediments, estuarine, and freshwaters) and man created or impacted habitats (e.g., wastewater treatment plants and agricultural soils). However, little is known on the plant‐species association of AOBs, particularly in the nutrient‐starved fynbos terrestrial biome. In this study, we evaluated the diversity of AOBs in the plant canopy of three South African fynbos‐specific plant species, namely Leucadendron xanthoconus, Leucospermum truncatulum and Leucadendron microcephalum, through the construction of amoA‐gene clone libraries. Our results clearly demonstrate that plant‐species specific and monophyletic AOB clades are present in fynbos canopy soils.